Of fake news and fake History - Souza, Rosali Fernandez de (2021)
This paper presents the Portuguese translation of a compilation of lectures by Professor Jason Steinhauer on the topic of fake news and its correlate, fake History, a concept coined by the author, to account for the strength with which obscurantism has striken and shaped the view on the past and the competence in History of the general public. The article analyzes correlations between the two issues that greatly weaken the public's ability to distinguish false from real information, and proposes a proactive communicative strategy on the part of historians, History Communication, a vital element to fighting the falsifying and unscientific discourse present in today’s main means of diffusion –especially in new technologies, news websites and social media – that uncritically associates History with the past.